Modified Weaver-Dunn Technique Using Transosseous Bone Tunnels and Coracoid Suture Augmentation. Issue 3 (1st February 2022) - Patel, Manan S.; Hill, Brian W.; Casey, Patrick; Abboud, Joseph A.
Abstract : Introduction: A modified Weaver-Dunn procedure for the management of acromioclavicular joint injuries that uses transosseous bone tunnels and coracoid suture augmentation is described with associated clinical results. Methods: A retrospective review of 39 consecutive patients who underwent a primary mWD procedure by a single surgeon from January 2013 to July 2019 was conducted. Patient charts and radiographs were reviewed for clinical course, complications and management, and radiographic evaluation. Satisfaction, American Shoulder and Elbow Surgeons (ASES), Single Assessment Numeric Evaluation, and Simple Shoulder Test scores were obtained. Results: A total of 28 patients (72%) with a mean follow-up of 37.5 (12 to 84 months) and a mean age of 44.3 ± 15.1 years were included. Postoperative ASES, Simple Shoulder Test, Single Assessment Numeric Evaluation, and satisfaction scores were 90.6 ± 14.2, 11.1 ± 1.5, 87.3 ± 10.2, and 4.4 ± 1.2 (out of 5), respectively, with a significant improvement in ASES of 42.2 ± 21.8 points ( P < 0.001). All patients had significant decrease in coracoclavicular distance ( P < 0.001). Three patients (10.7%) had complications, with two (7.1%) requiring additional surgery. Conclusion: Excellent functional and radiographic outcomes can be achieved with this modified Weaver-Dunn technique. Complication and revision rates are comparable with those that are found in the literature. Level of Evidence: Level IV, Retrospective cohort study